Analisis Putusan Permanent Court of Arbitration Terhadap Klaim Nine Dash Line: Studi Kasus Klaim Wilayah Natuna Utara - Maulana, Febriyansyah Rahmat; Repindowaty, Rahayu (Faculty of Law, Universitas Jambi, 2020)
The purpose of this research is to analyze the judgment of Permanent Court of Arbitration on Chinaâ€™s Nine Dash Line claim and Indonesiaâ€™s best strategies to resolve the claim of territory in Natuna Sea. In this study, qualitive methodes are used by taking various data and the source of the data to be verified. This research contains Chinese claim of â€œNine Dash Lineâ€ in the Natuna Islands which overlaps with the Indonesian Exclusive Economic Zone (EEZ). This Chinaâ€™s claim of â€œNine Dash Lineâ€ has been protracted for several years and is a serious problem in the region of South China Sea. In the conflict, researches revealed that Indonesia has various plans, efforts and attitudes so that territory of the Republic Indonesia is maintaned. The ruling of Permanent Court of Arbitration says that Chinaâ€™s claim of â€œNine Dash Lineâ€ are refutable and have no legal basis. But, china is rejects the ruling and still aggressive in the South Chine Sea which has potential to make instability in the region of South China Sea. The result of this study will show that the disputing state parties must implement and respect the ruling because it has became a source of international law. The ruling also has influence in dealing with chinese aggressiveness and regulation of maritimeâ€™s claim in the region of South China Sea.